2012
DOI: 10.1111/j.1399-3046.2012.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐haploidentical transplantations for primary immunodeficiencies: A single‐center experience

Abstract: SCID is characterized by profound deficiencies of T and B lymphocytes. HSCT is the only curative treatment for children with SCID. The clinical characteristics and outcome of 30 HLA-haploidentical transplantations in 18 patients (15 SCID, two Omenn syndrome, and one MHC Class II deficiency) are reported here. The age of patients at diagnosis ranged from one and half to nine months (median: four months). The median time was one month between the diagnosis and the time of the initial transplantation. Infused CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…A similar recent study in two Balkan countries reported only 15 SCID cases during a 24-year period [ 6 ]. Cipe et al [ 4 ] reported haploidentical HSCT in 18 patients in the capital city of Turkey during a 10-year period; however, many of these patients were from other regions of the country. Although four of our patients came from other regions (two with SCID, one with Omenn syndrome, and one with LAD), our patient numbers suggested that the prevalence of PID disorders should have been higher in the Black Sea Region of Turkey because of the high rate of consanguinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar recent study in two Balkan countries reported only 15 SCID cases during a 24-year period [ 6 ]. Cipe et al [ 4 ] reported haploidentical HSCT in 18 patients in the capital city of Turkey during a 10-year period; however, many of these patients were from other regions of the country. Although four of our patients came from other regions (two with SCID, one with Omenn syndrome, and one with LAD), our patient numbers suggested that the prevalence of PID disorders should have been higher in the Black Sea Region of Turkey because of the high rate of consanguinity.…”
Section: Discussionmentioning
confidence: 99%
“…These cases represented the first successful hematopoietic stem cell transplantation (HSCT) procedures, ushering in a new era of curative therapies for treating PID disorders [ 1 , 2 , 3 ]. To date, only one report has described HSCT therapies for PID disorders in Turkey [ 4 ]. The aim of this study was to retrospectively document all pediatric cases of patients diagnosed with PID disorders and considered for HSCT therapy at our pediatric transplantation center.…”
Section: Introductionmentioning
confidence: 99%
“…These data support that in consanguineous populations, AR forms of PIDs are more frequent as in Turkey. 17 A recent report 18 studied in a highly consanguineous population showed that (consanguinity rate was 81%) more than 90% of the diagnosed patients had AR disorders. In another study that included patients from Iran, 19 the consanguinity rate was 78% and the AR forms of PIDs were 63%.…”
Section: Discussionmentioning
confidence: 99%
“…6,15,[17][18] In this study, viral infections were observed in 16 of 20 patients (80%), with 14 patients (70%) developing CMV infection. Interestingly, all patients who had experienced CMV infection before transplant developed CMV reactivation after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][13][14][15] In this study, of the 6 SCID patients, 4 had an HLA-matched donor, only 1 patient had no infection before HSCT, and none of them underwent transplant before 5 months of age. It has been reported that SCID patients who receive transplants before the age of 3.5 months (95%) have a significantly higher survival rate than older children (76%).…”
Section: Discussionmentioning
confidence: 99%